Report of the Energy Survey of India Committee - Planning Commission (Planning Commission, 1965)
This report represents the results of the first official Energy Survey of India. It has been apparent for some time that an adequate supply of energy would be a key factor and play an important role in the national development of the country. Any shortage of energy will hold up the national planned economic growth. During the year 1962 and later, the matter . became one of increasing concern to the Government of India. At the same time, the requirements of the development of national power resources had come to form an increasingly large part of India’s requests for foreign aid. In consultation with Mr. Tyler Wood of the United States AID Mission, Mr. C.S. Krishnamurthy, then of the Indian Embassy in Washington, and on the advice of Mr. Walker Cisler of the Detroit Edison Company, Detroit, U.S.A., whose interest in these problems is well-known, it was agreed that a survey of the energy resources of India and her prospective needs would be of great advantage.
Government of India
Government of India